Interfaith Marriage in Indonesia: Judicial Interpretation of Surabaya District Court Decision No. 916/Pdt.P/2022/PN.Sby in the Perspective of Human Rights and Islamic Law Compilation - Pratama, Deo Agung (Berasan: Journal of Islamic Civil Law, 2025)
This article examines the legal reasoning and implications of the Surabaya District Court Decision No. 916/Pdt.P/2022/PN.Sby, which granted an application for interfaith marriage registration. Using a normative juridical and library research method, the study analyzes primary legal sources such as the Marriage Law No. 1 of 1974, Government Regulation No. 9 of 1975, the Compilation of Islamic Law (KHI), the Qur’an, and relevant Constitutional Court rulings, alongside secondary literature on human rights and family law in Indonesia. The findings reveal a deep legal tension: while Law No. 1/1974 and KHI prohibit interfaith marriage on religious grounds, the Population Administration Law (No. 23/2006) and subsequent judicial practices provide loopholes through civil registration upon court approval. From a human rights perspective, the decision was justified by invoking constitutional guarantees of freedom of religion and the right to form a family. However, from the standpoint of Islamic law and prevailing religious norms, the marriage lacks legal and spiritual validity. This study contributes to scholarly debates on legal pluralism, judicial activism, and the intersection between state law, religion, and human rights in Indonesia. It argues that inconsistent judicial interpretations not only undermine legal certainty but also raise broader questions about the harmonization of national law with religious doctrines in a plural society.